(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article explores the evolving institutional frameworks of environmental risk governance in the context of growing transnational threats such as climate change, biodiversity loss, and environmental degradation. Drawing on risk society theory, environmental governance, and multi-level institutionalism, the study presents a comparative analysis of developed and developing countries. It demonstrates that while developed states such as Germany, Japan, and Canada have embedded environmental policy into legally grounded, technologically advanced, and multi-actor governance systems, many developing countries continue to face fragmented institutions, limited autonomy, and external dependency. The article emphasizes that the effectiveness of environmental risk management is determined not solely by economic capacity, but by the political system’s ability to ensure long-term policy coherence, cross-sectoral coordination, and inclusive decision-making. The paper argues that institutional flexibility, digital infrastructure, and global integration are critical to transforming environmental risks into manageable governance challenges. By synthesizing theoretical and empirical perspectives, this research contributes to the discourse on ecological security and sustainable governance in the 21st century